Malaysian nurses’ views: Local versus Transnational Higher Education - Arunasalam, Nirmala Devi (Border Crossing, 2017)
This paper reports the findings of a study undertaken with Malaysian nurses who studied for a locally provided part-time post-registration top-up Nursing Degree versus those who studied on a Transnational Higher Education (TNHE) programme. Both types of programmes are bridging courses that allow registered nurses to upgrade their Diploma qualifications to Degree level. What is not sufficiently explored in available literature is nurses’ rationales for choosing a local programme over TNHE programme. Using hermeneutic phenomenology, six Malaysian nurses (chosen by snowball sampling method) were interviewed, in English and Bahasa Malaysia (Malaysian language). Thematic analysis was used to analyse data. The structure of the course and taught theory influenced the nurses’ choice to study on a local programme: the deciding factor was the practice component that ensured a theory-practice connection. The findings principally provide insights to TNHE providers and may guide them to enhance their teaching delivery, support and courses.